2015
DOI: 10.1128/jvi.02336-14
|View full text |Cite
|
Sign up to set email alerts
|

Identification of RISC-Associated Adenoviral MicroRNAs, a Subset of Their Direct Targets, and Global Changes in the Targetome upon Lytic Adenovirus 5 Infection

Abstract: Adenoviruses encode a set of highly abundant microRNAs (mivaRNAs), which are generated by Dicer-mediated cleavage of the larger noncoding virus-associated RNAs (VA RNAs) I and II. We performed deep RNA sequencing to thoroughly investigate the relative abundance of individual single strands of mivaRNA isoforms in human A549 cells lytically infected with human adenovirus 5 (Ad5) at physiologically relevant multiplicities of infection (MOIs). In addition, we investigated their relative abundance in the endogenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
71
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(74 citation statements)
references
References 44 publications
3
71
0
Order By: Relevance
“…Yet among mRNAs isolated from mivaRNA-containing RISC during Ad5 infection, seed sequences corresponding to mivaRNA II are underrepresented (Bellutti et al, 2015). Furthermore, both 3 -mivaRNA I (A) and (G) more efficiently knock down reporter gene expression than mivaRNAs derived from VA RNA II (Bellutti et al, 2015). Together these findings illustrate a disconnection between mivaRNA abundance in RISC and the likelihood that a given mivaRNA can knock down gene expression.…”
Section: Dicer Saturationmentioning
confidence: 95%
See 4 more Smart Citations
“…Yet among mRNAs isolated from mivaRNA-containing RISC during Ad5 infection, seed sequences corresponding to mivaRNA II are underrepresented (Bellutti et al, 2015). Furthermore, both 3 -mivaRNA I (A) and (G) more efficiently knock down reporter gene expression than mivaRNAs derived from VA RNA II (Bellutti et al, 2015). Together these findings illustrate a disconnection between mivaRNA abundance in RISC and the likelihood that a given mivaRNA can knock down gene expression.…”
Section: Dicer Saturationmentioning
confidence: 95%
“…While these mivaRNAs are the predominant RISC-associated miRNAs of viral origin during Ad5 infection (Bellutti et al, 2015), a small fraction of adenoviral miRNAs are thought to originate from RNAs other than VA RNA (Zhao et al, 2013). While one group reported that approximately 80% of Ago-2-containing RISC complexes late in AdV infection contain mivaRNAs (Xu et al, 2007), others report a significantly lower proportion, 15% (Bellutti et al, 2015).…”
Section: Dicer Saturationmentioning
confidence: 99%
See 3 more Smart Citations